PERANAN SAYID OSMAN SYAHABUDDIN BIN ABDURRAHMAN DI KERAJAAN SIAK (1766-1810) - Tika Novita Sari; Isjoni '; Tugiman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: Historiography of Siak not only discuss about the process ofgrowing and developing, it also has been recorded the ebbtide incidents faces by SiakEmpire and about characters who have a lot of role in the course of Siak Empire. Bywriting about character who have a lot of roe in the course of Siak Empire. By writingabout character that has been fighting, people will know deeper and respect to the effortof the fighters in maintaining Siak Empire. Adviser of Sultanis one of the characters thathas important role in helping sultan to run the government. In history of Siak empire,Sayid Osman Syahabuddin bin Abdurrahman is one of one the adviser that have took apart in developing Siak Empire. The purposes of this study are: (1) To reveals thehistory lives of Sayid Osman Syahabuddin as character who took a part in Siak Empire,(2). To discovers the role of Sayid Osman Syahabuddin as sultan adviser in SiakEmpire, (3) To finds out the other roles of Sayid Osman Syahabuddin including assultan adviser.This study used the historical method or historic. The data were collectedthrough library studies and interviews. This study started from the submission of title ofproposal until the last revision of this study was done by the writer. The result of thisstudy showed that Sayid Osman Syahabuddin had important role in raising anddeveloping Siak Empire. As someone who has wide knowledge, Sayid OsmanSyahabuddin gave many advices to Sultan in developing Siak Empire. Moreover, SayidOsman Syahabuddin was a skilled commander of war and he also was a clergy whotook a part in deepening and consolidating belief of people in Siak Empire about IslamReligion.Keywords: Role, Adviser, and Siak Empire.